The ICD‐11 developmental field study of reliability of diagnoses of high‐burden mental disorders: results among adult patients in mental health settings of 13 countries. Issue 2 (June 2018) - Reed, Geoffrey M.; Sharan, Pratap; Rebello, Tahilia J.; Keeley, Jared W.; Elena Medina‐Mora, María; Gureje, Oye; Luis Ayuso‐Mateos, José; Kanba, Shigenobu; Khoury, Brigitte; Kogan, Cary S.; Krasnov, Valery N.; Maj, Mario; et al.
Abstract : Reliable, clinically useful, and globally applicable diagnostic classification of mental disorders is an essential foundation for global mental health. The World Health Organization (WHO) is nearing completion of the 11th revision of the International Classification of Diseases and Related Health Problems (ICD‐11). The present study assessed inter‐diagnostician reliability of mental disorders accounting for the greatest proportion of global disease burden and the highest levels of service utilization – schizophrenia and other primary psychotic disorders, mood disorders, anxiety and fear‐related disorders, and disorders specifically associated with stress – among adult patients presenting for treatment at 28 participating centers in 13 countries. A concurrent joint‐rater design was used, focusing specifically on whether two clinicians, relying on the same clinical information, agreed on the diagnosis when separately applying the ICD‐11 diagnostic guidelines. A total of 1, 806 patients were assessed by 339 clinicians in the local language. Intraclass kappa coefficients for diagnoses weighted by site and study prevalence ranged from 0.45 (dysthymic disorder) to 0.88 (social anxiety disorder) and would be considered moderate to almost perfect for all diagnoses. Overall, the reliability of the ICD‐11 diagnostic guidelines was superior to that previously reported for equivalent ICD‐10 guidelines. These data provide support for the suitability of the ICD‐11 diagnostic guidelines for implementation at a global level. The findings will inform further revision of the ICD‐11 diagnostic guidelines prior to their publication and the development of programs to support professional training and implementation of the ICD‐11 by WHO member states.